2020
DOI: 10.1017/wsc.2020.31
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic resistances to atrazine and mesotrione in a multiple-resistant waterhemp (Amaranthus tuberculatus) population

Abstract: Metabolic resistances to atrazine (atz-R) and mesotrione (meso-R) occur in several waterhemp [Amaranthus tuberculatus (Moq.) Sauer] populations in the United States. Interestingly, although metabolic atz-R but mesotrione-sensitive A. tuberculatus populations have been reported, an Amaranthus population has not been confirmed as meso-R but atrazine-sensitive, implying an association between these traits. Experiments were designed to investigate whether the single gene conferring metabolic atz-R plays a role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…For this reason, and because of already widespread atrazine resistance, it was not particularly surprising that HPPD‐inhibitor‐resistant A. tuberculatus populations routinely were reported to also be resistant to atrazine 28 . A very recent report, however, indicates there may be a physiological basis for this association 75 . Specifically, in a segregating F 2 population, plants that were atrazine resistant were more likely to be resistant to mesotrione, and all plants resistant to mesotrione were atrazine resistant.…”
Section: Resistance To Specific Herbicide Groupsmentioning
confidence: 98%
See 2 more Smart Citations
“…For this reason, and because of already widespread atrazine resistance, it was not particularly surprising that HPPD‐inhibitor‐resistant A. tuberculatus populations routinely were reported to also be resistant to atrazine 28 . A very recent report, however, indicates there may be a physiological basis for this association 75 . Specifically, in a segregating F 2 population, plants that were atrazine resistant were more likely to be resistant to mesotrione, and all plants resistant to mesotrione were atrazine resistant.…”
Section: Resistance To Specific Herbicide Groupsmentioning
confidence: 98%
“…28 A very recent report, however, indicates there may be a physiological basis for this association. 75 Specifically, in a segregating F 2 population, plants that were atrazine resistant were more likely to be resistant to mesotrione, and all plants resistant to mesotrione were atrazine resistant. The investigators proposed that the gene (likely AtuGSTF2) conferring atrazine resistance contributed to mesotrione resistance.…”
Section: Hppd Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the combination of HPPD-inhibitors with other MOA increases the spectrum of weed control and delays the evolution of herbicide resistance, which will allow future use of currently effective MOA. The occurrence of MHR waterhemp resistant to both HPPD-inhibitors and atrazine (Jacobs et al, 2020;McMullan & Green, 2011) as well as Palmer amaranth Jhala et al (2014) suggests these herbicides should be used strategically, and growers should strive for 100% control. The ability of MHR waterhemp to escape herbicide applications, germinate late in the growing season, produce a plethora of viable offspring and evolve resistance to multiple herbicide MOA necessitates full-season control programs.…”
Section: Corn Injury and Yieldmentioning
confidence: 99%
“…Indeed, numerous studies have pointed towards cytochrome P450s as being pivotal for resistance to the herbicide group 815 . Recently, Jacobs et al reported a tight association between resistance to atrazine and a component of a complex HPPD-inhibitor resistance phenotype in A. tuberculatus 44 . While atrazine resistance in the tested population is mediated by a glutathione S -transferase (Ma et al 2013), the mechanism of resistance to HPPD-inhibitors is unknown.…”
Section: Discussionmentioning
confidence: 99%